Breathe in, breathe out : restore your health, reset your mind and find happiness through breathwork - Sandeman, Stuart (Hanover Square Press, 2022)
Stuart Sandeman reveals the hidden power of breathing and how, by changing the way you breathe, you can transform the way you think and feel. Since tragic loss brought him to breath work, Stuart has changed the lives of thousands through his signature sessions. Now he wants the same for you. Whether you want focus or flow, more energy or less anxiety, Stuart can tell you how to get it. Combining modern science and ancient wisdom, he sets out how to stay on top of your game, overcome a negative mindset and heal from your past. You'll learn to deepen the connection with yourself, others and the world around you.